Profile of Intensive Care Unit admission and Outcomes of Medical and Surgical patients at A Tertiary Government Hospital: A 5 Year Trend Analysis - Ahmed, Shakera; Yusuf, Omar Faruque; Alam, AKM Shamsul; Awal, Anisul (Bangladesh Journal of Medicine, 2018)
Background: The intensive care unit (ICU) is that part of the hospital where critically ill patients that require advanced airway, respiratory and haemodynamic supports are usually admitted. Intensive care unit admissions which aim at achieving an outcome better than if the patients were admitted into other parts of the hospital however come at a huge cost to the hospital, the personnel and patients’ relations. Objective: To audit the 5 year bed occupancy rate and outcome of medicine and surgical patients admitted into the ICU of the Chittagong Medical College Hospital, Chittagong, Bangladesh. Design: A 5 years retrospective study (Record review) from January 2012 to December 2016. Method: Data were extracted from the ICU records of the patient and analyzed. Results: During this study period, the frequency of admission into ICU was significantly more (p<0.001) from medical discipline (55.20%) than surgical disciplines (44.80%). The incidence of survival was significantly lower (p<0.001) from medical discipline (37.68%), than from surgical disciplines (49.05%). Occurrence of total ventilatory support provided in all disciplines was 60.32% and it was significantly higher for the surgical patients. Overall mortality rate was 57.23%. Conclusion: During prioritizing the patients for ICU admission surgical cases should get preference. It is primarily necessary to optimize patient to doctor ratio and patient to nurse ratio and providing the service by critical care physicians (“intensivists”) to reduce the mortality rate of ICU. Bangladesh J Medicine Jul 2018; 29(2) : 59-62